PERCEPTION OF RESIDENTIAL CONDITIONS AS AN ONLINE LEARNING SPACE Comparative Study Of Residences In Yogyakarta And Bandung - Noviandri, Patricia Pahlevi; Sudarsono, Anugrah Sabdono (Border: Jurnal Arsitektur, 2023)
The condition of living plays a vital role in the online learning process at home. The residential need for support in the learning process was seen when Covid-19 forced students to study from their residences. However, residences not designed for students to carry out the learning process from home result in the focus/concentration in the process not running well. The study aims to explore the dimensions of residential perception that are by online learning needs. This study uses a quantitative approach with PCA analysis to find dimensions that need to be considered in the residence so that the learning process from home can run well. This study used student respondents living in Yogyakarta and Bandung so that the results of this study have a comparison of student perceptions in two different cities. The dimensions of perception of living conditions for online learning are audial quality, space comfort, space performance, and visual quality. Living conditions have differences in perception according to the type of residence in the form of boarding houses and houses. Ultimately, this study provides design principles that need to be considered in today’s residential design.